Pengaruh Modal Sosial, Modal Manusia, Biaya Transaksi Terhadap Kesuksesan UMKM Industri Seni Lukisan Di Kabupaten Buleleng - I Komang Edy Atmaja; I Gusti Ayu Purnamawati (Universitas Pendidikan Ganesha, 2020)
The purpose of this research is to examine the effect of social capital, human capital and transaction costs on the success MSMEs by taking a sample of 31 MSMEs employees engaged in the painting industry in Buleleng Regency. The research data were obtained from the results of the distribution of questionnaires that had gone through a process of testing and testing the reliability of the instrument. Data from the questionnaires were further analyzed using multiple linear regression analysis techniques with the help of the SPSS program. Based on the results of the analysis in this study, the results of the analysis show that social capital has a positive and significant effect on the success of MSMEs, this indicates that the higher the social capital of MSMEs employees, the higher the success of MSMEs, the results of the second analysis show that human capital has a positive and significant effect on success , this shows that the high human capital will encourage the success of MSMEs, then the third result in this study shows that the transacion cost has a negative and significant effect on the success of MSMEs, this shows that the high transaction costs incurred by MSMEs will reduce the success of MSMEs